El habla y la pedagogía: particularidades en la interacción de una clase idiomas (2021)
This paper aims at identifying some of the main features that a language classroom possesses regarding interaction. Conversation analysis was used to approach classroom talk and build reflection and understanding. For data to be gathered, a language lesson conducted in a public university with adult students was video recorded, divided in chunks and transcribed. Three extracts from the lesson were taken as a source of analysis and issues as identity, repair and turn taking presented on them were identified. Findings made evident the co-construction of interaction and how it can affect or modify the identities performed by participants. Besides, allowing students to do self-repair arise as relevant actions to carry on for promoting more meaningful and authentic interaction.